Changes of mucosa microflora obligate representatives at the first year life children, living in Kursk during 2007-2012 - A. V. Ageychenko; I. D. Lifirenko; O. A. Medvedeva; P. V. Kalutsky (Кубанский научный медицинский вестник, 2014)
Impact of exogenous and endogenous factors leads to disruption of intestinal endoecology which often expressed quantitative changes of bifidobacteria and Lactobacteria. The aim of investigation was to study large intestine microbiocenosis at the first year life children, living in Kursk. We analyzed the results of bacteriological studies of feces, taken between 2007 and 2012 from 273 children, living in Kursk with a preliminary diagnosis of «dysbiosis». it was been established that in Kursk during 2007-2012 children of first year life were significantly more registered dysbiosis due to a total absence or reduction in the number of bifidobacteria. Also in all the studied children was detected disbalance of normal flora.